The Prevalence and Impact of Migraine and Severe Headache in the United States: Figures and Trends From Government Health Studies. Issue 4 (12th March 2018) - Burch, Rebecca; Rizzoli, Paul; Loder, Elizabeth
Abstract : Background and Objectives: In this targeted systematic review, we aimed to identify up‐to‐date prevalence estimates of migraine and severe headache in adults from population‐based US government surveys. Our goal was to assess the stability of prevalence estimates over time, and to identify additional information pertinent to the burden and treatment of migraine and other severe headache conditions. Methods: We searched for the most current publicly available summary statistics from the National Health Interview Survey (NHIS), the National Hospital Ambulatory Medical Care Survey (NHAMCS), and the National Ambulatory Medical Care Survey (NAMCS). We extracted and summarized data from each study over time and as a function of demographic variables. Results: The prevalence and burden of self‐reported migraine and severe headache in the US adult population is high, affecting roughly 1 out of every 6 American and 1 in 5 women over a 3‐month period (15.3% overall [95% CI 14.75‐15.85], 9.7% of males [95% CI 9.05‐10.35] and 20.7% of females [95% CI 19.84‐21.56]). The prevalence has been remarkably stable over a period of 19 years. The prevalence of migraine or severe headache in 2015 was highest in American Indian or Alaska Natives (18.4%) compared with whites, blacks, or Hispanics, with the lowest prevalence in Asians (11.3%). There is a higher burden of migraine in those aged 18‐44 (17.9%), people who are unemployed (21.4%), those with family income less than 35, 000 per year (19.9%), and the elderly and disabled (16.4%). Headache is consistently the fourth or fifth most common reason for visits to the emergency department, accounting for roughly 3% of all emergency department visits annually. In reproductive aged women, headache is the third leading cause of emergency department visits. Conclusions: Severe headache and migraine remain important public health problems that are more common and burdensome for women, particularly women of childbearing age, and other historically disadvantaged segments of the population. These inequities could be exacerbated if new high‐cost treatments are inaccessible to those who need them most.